First population study of the general public awareness and perception of epilepsy in Croatia - Bagić, Anto (Array, 2009)
Public knowledge of, perception of, and attitudes toward epilepsy in Croatia were assessed for the first time by asking 1000 randomly selected adults 12 questions. Ninety-seven percent of respondents had heard about epilepsy, 55% knew someone with epilepsy, and 44.6% had witnessed a seizure. Interviewees were quite ready to accept a person with epilepsy. Approximately 7% would object if their child played with a child with epilepsy, and 76% believed that a child with epilepsy could succeed as well as a child without epilepsy. Although 52.5% would approach a seizing person and help, 33.1% would call ‘ ‘ 911.” Positive attitude correlated with knowing someone with epilepsy and/or witnessing a seizure. General awareness of epilepsy in Croatia approaches that of other developed countries, and the majority of the population expressed acceptance of and readiness to help people with epilepsy. These results are more favorable than expected and an encouraging foundation for further improvements in social acceptance of persons with epilepsy.